Effect of Climate Change on Agricultural Productivity in Nigeria (1991-2022) - Oghenekevwe, Oru Patricia; ADESOYE, Opeyemi Sodeeq (The Es Economics and Entrepreneurship, 2024)
This research work examines the effect of climate change on the agricultural productivity in Nigeria from 1991 to 2022, a period of 32 years. This research work applies the Sustainable Livelihood Theory as a theoretical framework and an Autoregressive Distributed Lag Model (ARDL) was estimated. The data used in the research work was sourced from Central Bank of Nigeria Statistical Bulletin of 2022 and the World Bank Data Bank on Agricultural GDP, Rainfall, Temperature and Carbon Emissions. The Unit root test and the bounds test were employed to check for the stochastic properties of the series and the presence of a long run relationship between the variables. The results showed that climate change variables (rainfall, temperature and carbon emissions) all exert a negative effect on agricultural productivity in both short and long run. The Error Correction Mechanism revealed that a disequilibrium in climate change can be corrected at a speed of 8% annually. In the light of the empirical evidence regarding the negative effect of climate change on agricultural productivity, it is recommended that there should be existence of institutional support system that will aid farmers in further understanding anticipated climate change which will help cushion the effect of climate change.